IMPLEMENTASI MAQASID SYARIAH PADA ANNUAL REPORTBANK UMUM SYARIAH SEBAGAI MITRA UNIVERSITAS ISLAMI(STUDI KASUS PADA BANK SYARIAH MANDIRI) - Frisztina Anisa; Veni Soraya Dewi; Ade Vira Agustina (Profetika: Jurnal Studi Islam, 2020)
Islam has arranged all matters relating to human life in the world, including economic activities. In carrying out economic activities must be in accordance with the purpose of life of a Muslim with its implementation is mashlahah on the activities of maqasid syaria. Maqashid sharia has five factors, namely guarding religion, guarding the soul, guarding reason, guarding offspring, and protecting property. Sharia Commercial Bank as a supporter of the community’s economy in carrying out all its activities must be based on sharia provisions. Annual Report reflects the activities of Sharia Commercial Banks both financial and non-financial. Maqasid Sharia as an indicator of the implementation of sharia principles must be reflected in the Sharia Commercial Bank Annual Report. This study aims to determine the implementation of the Maqasid Syaria in the Sharia Commercial Bank annual report. The sample in this study is Bank Syariah Mandiri Annual Report. The research method used in this study is qualitative research that is descriptive research and analysis based on theories and other supporting sources. The results of the study are Bank Syariah Mandiri has implemented all aspects of the maqasid syaria as reflected in the Annual Report.